PARE0012 The french patient's association aflar: has generated the french national alliance against osteoporosis and the first general convention for osteoporosis, that is a campaign to create a national promoting tool to improve the management of osteoporosis.: 7 priorities to better treat patients i. (12th June 2018) - Grange, L.; Cortet, B.; Thomas, T.; Srour, F.; Guggenbuhl, P.; Roux, C.; Monod, P.; Feron, J. M.; Alliot- launois, F.; Tremollières, F.; Chalés, G.; Giraud, J.; et al.
Abstract : Background: Osteoporosis is a major public health issue with 5 million of French affected. Overall, she seriously underestimated, and costs are barely covered in France. Considering this situation, AFLAR were urged to create the so-called National Osteoporosis Alliance made up of 15 various stakeholders and patients. Methods: National consultations on osteoporosis rely methodologically on 2 pillars:First the bottom-up reporting on patient needs and expectations. Second the conduct of coordination meetings with various osteoporosis key stakeholders and patients as part of regional panel-discussions. The aim is to provide an overview of real obstacles contributing to the lack of government subsidies for osteoporosis and write consensual proposals compiled into a white paper. Results: An online survey along with a citizen's panel were key to provide feedbacks on difficulties, knowledges and believes but also patient needs. From November 2016 to June 2017, 10 days of dialogue and debate covering 5 various topics were convened in 10 different cities: Consultation and consolidation work regarding proposals made during various panel-discussions allowed synthesis around one call: the creation of a real public health plan against osteoporosis-related fractures relying on 7 key axis. Conclusions: The human and medico-economic rational considering dramatic fallouts caused by osteoporosis has been illustrated many times over. The policy makers mobilization made by stakeholders through white paper release, a real manifesto for public health plan against osteoporosis-related fracture, remain a significant challenge to face. Disclosure of Interest: L. Grange Grant/research support from: ucb Lilly Amgen expanscience Roche company, B. Cortet : None declared, T. Thomas : None declared, F. Srour : None declared, P. Guggenbuhl : None declared, C. Roux : None declared, P. Monod: None declared, J. M. Feron: None declared, F. Alliot- launois: None declared, F. Tremollières : None declared, G. Chalés : None declared, J. Giraud : None declared, E. Senbel: None declared, G. Thibaud: None declared, P. Niemczynski: None declared, D. R. Bertholon : None declared, C. F. Roques : None declared, D. Buchon: None declared, C. Bonnet : None declared, H. Blain : None declared, C. Rolland : None declared, D. Lafarge : None declared, L. Carton: None declared